2012
DOI: 10.1637/10197-041012-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza Virus Investigation in Wild Bobwhite Quail from Texas

Abstract: The objective of this study was to determine the prevalence of avian influenza viruses (AIV) in bobwhite quail (Colinus virginianus) populations from the rolling plains of Texas, U. S. A. A total of 1320 swab samples (652 tracheal swabs and 668 cloacal swabs) and 44 serum samples were collected from wild-captured or hunter-harvested bobwhite quail from November 2009 to April 2011 at the Rolling Planes Quail Research Ranch, Fisher County, Texas, U. S. A. The presence of AIV in the swabs was determined by real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
2
0
2
Order By: Relevance
“…Our data showed that AIVs were not detected in either oralorcloaca swabs of all quails. Similar results were clarified by Ferro et al (2012) who mentioned that no virus was isolated from any of the suspicious samples tested. This finding might be attributed to short term of sample collection (autumn season).…”
Section: Discussionsupporting
confidence: 79%
“…Our data showed that AIVs were not detected in either oralorcloaca swabs of all quails. Similar results were clarified by Ferro et al (2012) who mentioned that no virus was isolated from any of the suspicious samples tested. This finding might be attributed to short term of sample collection (autumn season).…”
Section: Discussionsupporting
confidence: 79%
“…No antibodies to H5 or H7 IAVs were detected. A similar study of wild bobwhite quail ( Colinus virginianus ) in Texas, US from 2009–2011 tested 652 tracheal swabs, 668 cloacal swabs, and 44 serum samples from wild-captured and hunter-harvested bobwhite quail [ 47 ]. No virus was isolated and no antibodies reactive to IAV were detected, but 13 cloacal swabs and 5 tracheal swabs were positive for viral RNA by rRT-PCR, with another 100 swabs showing suspect positive results (Ct > 35).…”
Section: Pheasants Turkeys Peafowl Old World Quail New World Qmentioning
confidence: 99%
“…Перепелів також використовують у дослідницьких цілях як модельну тварину, наприклад, для визначення дії токсикантів, зокрема аеробних плісеневих міксоміцетів класу Deuteromycetes (Orobchenko, 2019). На думку окремих вчених, за рахунок підвищеної температури тіла, порівняно з курми, на 2 °С, перепели стійкі до низки захворювань, вони несприйнятливі до хвороб лейкозного комплексу (Ferro et al, 2012;Morris et al, 2020).…”
Section: продукція перепелівництва користується попитом вunclassified